A Strategic Analysis of Import of the WTO Accession on China's Telecommunications Industry - Lei, Zhang (2007)
The dissertation is divided into two parts, namely, an overview of China's telecommunications industry and the strategic analysis of the influence of China's telecom industry accession to the WTO. Based on the several strategic management classical frameworks, the main aim of this piece of research is to analyze the external and internal environment of China's telecommunication industry and the impact of China's entry into WTO on this industry. Specifically, this aim is decomposed into the following research objectives. First, we use PEST framework to examine the external environment of China's telecommunication industry. It is the external factors such as political and economic environment that shape today's telecommunication industry of China. Second, we use Five-Force framework to explore the internal 7 A Strategic Analysis of the Impact of the WTO Accession on China's Telecommunication Industry environment of China's telecommunication sector. Factors to be analysed include rivalry, new entrants and competition and so forth. Third, we investigate the impact of China's entry into the WTO on China's telecommunication industry. We will focus on how the gradual openness of the industry to foreign investors and foreign competition will reshape China's telecommunication industry. Lastly, we will discuss the strategy of China's telecommunication industry and off our recommendations. It needs to be clarified that by telecommunication industry in this dissertation we mean the operation industry of telecommunication, not the equipment industry of telecommunication. The equipment industry is very different from the operation industry of telecommunication. For example, the competition environment of the two sectors is very different. The equipment segment of China's telecommunication industry has been open to foreign competition in the form of inward foreign direct investment for instance for a long time. In contrast, the operation arm of the industry has been protected from foreign investors competition by the government up until today.